2016
DOI: 10.1007/s10393-016-1149-1
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella in Wild Birds Utilizing Protected and Human Impacted Habitats, Uganda

Abstract: As human populations in Africa expand, humans encroach and modify wildlife habitats for farming, fishing, tourism, or settlement. Anthropogenic activities in shared environments may promote transmission of zoonotic pathogens between humans, domestic animals, and wildlife. Between July 2012 and February 2014, we evaluated Salmonella prevalence, serovars, genotypes, and antibiotic resistant phenotypes in resident and migratory birds utilizing human-impacted habitats in northwestern Lake Victoria and protected ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
1
7
1
1
Order By: Relevance
“…As in other countries ( 16 , 27 29 ), genomic analysis provided evidence that wild birds are a source of human infection with DT160. No characterized antimicrobial resistance genes were detected in any of the DT160 draft genome sequences, suggesting low or no antimicrobial resistance, consistent with other Salmonella strains found in wild birds ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 80%
“…As in other countries ( 16 , 27 29 ), genomic analysis provided evidence that wild birds are a source of human infection with DT160. No characterized antimicrobial resistance genes were detected in any of the DT160 draft genome sequences, suggesting low or no antimicrobial resistance, consistent with other Salmonella strains found in wild birds ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 80%
“…Although the environment is the main source of Campylobacter and Salmonella contamination of animal foods due to unhygienic handling, the potential of accidental intestinal contents spillage and extra‐gastrointestinal colonization as a source of contamination should not be underestimated (Humphrey & Williams, ). The extended interactions between humans and animals mostly observed with pet animals and their owners, extensive animal husbandry, animal handlers and wildlife habitat encroachment predispose humans to animal‐associated infections (Afema & Sischo, ; Behravesh et al, ; Holmberg, Rosendal, Engvall, Ohlson, & Lindberg, ). Animals shedding Campylobacter and Salmonella contaminate environments including soil, manure, aquatic environments and water sources which increase the risk of humans acquiring infection when hygiene practices are not well‐observed (Whiley, Akker, Giglio, & Bentham, ; Table ).…”
Section: Public Health Risks Associated With Animals Colonized and Shmentioning
confidence: 99%
“…This showed that S. Ouakam species circulating in the region shares has the same ancestor with the ones reported from the USA. This may be due to importation of animal food ingredients from the US, migration of wild birds (35), etc.…”
Section: Resultsmentioning
confidence: 99%